PEMBERDAYAAN MASYARAKAT PENGRAJIN GRABAH KASONGAN DI TENGAH PANDEMI COVID-19 - Irma, Tiza; Atmojo, Muhammad Eko (Jurnal Pemerintahan dan Kebijakan (JPK), 2022)
This study aims to see community empowerment in strengthening MSMEs for pottery craftsmen in Kasongan, Bantul in the midst of the COVID-19 pandemic. Because as is known that the COVID-19 pandemic is enough to cause a multidimensional crisis that has a very significant impact on economic movements. So that this economic sector feels a considerable impact from the COVID-19 pandemic, coupled with the various policies carried out by the Indonesian government. One of the affected sectors is the MSME sector located in Kasongan, Bantul.  During the COVID-19 pandemic, MSME players, especially the pottery craftsmen MSME group, were also affected where there was a decrease in pottery sales turnover and also a decrease in pottery production. However, the pottery craftsman MSME group was able to survive amid the uncertainty of the covid-19 pandemic. This is certainly influenced by several things, one of which is the efforts of the village government itself in empowering the community in strengthening MSMEs. Therefore, to determine community empowerment in strengthening MSMEs in the midst of the COVID-19 pandemic, researchers used qualitative research methods with descriptive analysis. So that it can see the social phenomena that occur directly and more deeply. From this study, the results were obtained that if you look at the empowerment of the three phases of empowerment, namely the Initial Phase, the Participatory Phase, and the Emancipatory Phase, then the empowerment of the community in Bangunjiwo for pottery MSME actors can be said to be successful. So that with these 3 phases, it can strengthen Kasongan pottery craftsmen to survive in the midst of the COVID-19 pandemic